RAGAM TEKNIK PENERJEMAHAN FRASA NOMINA DALAM NOVEL MAWÄ€KIBUL-ACHRÄ€R KARYA AL-KAILANI: SEBUAH PENDEKATAN TEORI ILMU PENERJEMAHAN ARAB - Muhammad Yunus Anis, Mahyudin Romadhan (Jurnal CMES, 2016)
This Research discusses the variations of noun phrase translation types and the technique of translating noun phrase on novel â€œMawÄkibul-AchrÄrâ€ written by AlKailÄnÄ«. Methode of the research was descriptive qualitative. The source of the data research which describe the type and the technique of translation of noun phrase on novel â€œMawÄkibul-AchrÄrâ€ written by Al-KailÄnÄ«. Based on the research it can be concluded that: First, there are three variations of noun phrase type named: naÊ»ty, idhÄfy, and combination of both. Second, the techniques used to translate of noun phrase were 13 translation techniques.